PEMBINGKAIAN BERITA POLITIK DALAM PEMILIHAN KEPALA DAERAH (ANALISIS FRAMING BERITA PEMILIHAN WALIKOTA PEKANBARU DI SURAT KABAR TRIBUN PEKANBARU DAN RIAU POS) - Boyke Maventa Sihombing; Belli Nasution (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
The simultaneous elections held on February 15, 2017 were a party of Indonesian democracy. election of regional headwas held simultaneously in one hundred regions with seven provinces, eighteen cities and seventy-six districts. Of the eighteen cities, Pekanbaru includes being a city that organizes election of regional head simultaneously with five candidate pairs. Pekanbaru election news attracted attention, especially the biggest newspaper in Riau and Pekanbaru namely Tribun Pekanbaru and Riau Pos. Both media have different ideologies because they have their respective interests, to see that it takes a study of framing analysis of Pan and Kosicki. This study aims to determine the elements of news structure and representation of media ideology Tribun Pekanbaru and Riau PosThis research is a qualitative research with framing analysis approach. Subjects in this study are editorial tools and journalists news authors Selection of Pekanbaru Mayor selected with purposive sampling technique. This study uses data collection techniques with observation, interview and literature study. To view the validity of data, the author uses an opt-in extensionThe results obtained are, first News in Tribune Pekanbaru Title, the news terrace has described the contents of the news. The balance of the news is visible with relevant sources. News Riau Pos puts the title that attracts the reader's attention, the news is also no doubt his balance. Proof of visualiasi is sometimes omitted or inconsistent with pre-published news.second Tribun Pekanbaru with their independent and credible for preaching the election mayor of Pekanbaru guaranteed. However, they have an economic interest. Riau Pos proclaimed not a media that has any interest in preaching the Mayor election Pekanbaru. Although in its presentation, more dominate Incumbent couples.Keyword : election of regional headwas, of framing analysis of Pan and Kosicki